Habilidades de aprendizaje en Física de la carrera de Pedagogía de las Ciencias Experimentales: Matemáticas y la Física. - Yuquilema Caizaguano, Willian Alejandro (2024)
The current research entitled “Learning Skills in Physics of the Pedagogy of Experimental Sciences, Mathematics, and Physics” career aims to determine the levels of development of learning in skills in Physics of the students of the Pedagogy of experimental Mathematical Sciences and Physics at Universidad Nacional de Chimborazo. Reading the methodology, the researcher chose a quantitative approach with a non-experimental design at a descriptive level. The population consisted of Pedagogy of Experimental Mathematical Sciences and Physics students at Universidad Nacional de Chimborazo. A stratified sampling procedure was applied to obtain the sample. It was necessary to use a test as an instrument to obtain the data. Once the researcher conducted the data analysis, it was evident that students learning skills improved as they progressed to higher semesters. It is advisable that teachers, during the teaching-learning process in the area of Physics, provide students with exercises that strengthen learning skills to speed up learning and obtain better academic performance.